SPIRITUAL LEADERSHIP: THE CASE OF INSTILLING VALUES IN STUDENTS THROUGH THE KIAI’S PROGRAM IN THE GLOBALIZATION ERA - Fikriyah Fikriyah; Abdul Karim; Muhamad Khozinul Huda; Anih Sumiati (Universitas Gadjah Mada, 2021)
Introduction: Value coaching is an inseparable part of education, which can be a powerful means of warding off negative influences in the globalization era. Main objectives: Regarding the importance of value coaching, this study aims to describe Kiai's leadership program in building a value system in Islamic boarding schools (IBS). Background problems: The study was also conducted in response to the existing symptom among young people that shows their ignorance of values and morals in social manners. Novelty: The study on Kiai’s program is intended to cover a value system based on transcendent values in instilling the students’ values. Research Method: This research used a qualitative method, and the research subjects consisted of Kiai, Ustadz (teacher), and Santri (students). The data were obtained through interviews, observation, and documentation. The data were then validated by triangulation and processed through data reduction, data display, and conclusion drawing. Findings: The results revealed that the role of the Kiai had designed the value system program from upstream to downstream for IBSs. Conclusion: It is concluded that the projection of Islamic boarding schools in the future is the idealism of the Kiai's thinking, which continues to change and develop in line with the development of the IBSs. This finding's implication is the importance of systematic follow-up of value system implementation to achieve better goals.